Pengembangan LKPD Berbasis PBL Pada Materi Sistem Gerak Manusia - Reina Harahap; Miza Nina Adlini (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop a Problem Based Learning (PBL)-based Student Worksheet (LKPD) to improve students' problem-solving skills on the topic of the human movement system. This study employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at MAS Aisyiyah Medan involving subject matter experts, language experts, media experts, biology teachers, and 32 eleventh-grade students. Data were collected through observations, interviews, validation questionnaires, response questionnaires, documentation, and problem-solving skills tests. The developed product was assessed based on validity, practicality, and effectiveness. The validation results showed that the LKPD obtained a very high feasibility level, with a percentage of 94.64% from the subject matter expert, 96.15% from the language expert, and 96.15% from the media expert. The implementation results showed an increase in students' average scores from 49.7 in the pretest to 71.9 in the posttest, with an N-Gain score of 0.44, which was categorized as moderate. Therefore, the PBL-based LKPD developed in this study was declared valid, practical, and sufficiently effective in improving students' problem-solving skills in biology learning. Keywords: Human Movement System, Problem Based Learning, Problem-Solving Skills, Student Worksheet